Perspectives on PARP Inhibitor Combinations for Ovarian Cancer - Bonadio, Renata Colombo; Estevez-Diz, Maria del Pilar (Frontiers in Oncology, 2021)
Poly (ADP-ribose) polymerase (PARP) inhibitors constitute an important treatment option for ovarian cancer nowadays. The magnitude of benefit from PARP inhibitors is influenced by the homologous recombination status, with greater benefit observed in patients with BRCA mutated or BRCA wild-type homologous recombination deficient (HRD) tumors. Although some PARP inhibitor activity has been shown in homologous recombination proficient (HRP) ovarian tumors, its clinical relevance as a single agent is unsatisfactory in this population. Furthermore, even HRD tumors present primary or secondary resistance to PARP inhibitors. Strategies to overcome treatment resistance, as well as to enhance PARP inhibitors' efficacy in HRP tumors, are highly warranted. Diverse combinations are being studied with this aim, including combinations with antiangiogenics, immunotherapy, and other targeted therapies. This review discusses the rationale for developing therapy combinations with PARP inhibitors, the current knowledge, and the future perspectives on this issue.